Engagement Strategies and Academic Performance of the Learners in Online Distance Learning, Zone 3, Division of Zambales - Evangelista, Gladys D.; Sepillo, Geoffrey S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
This study aimed to determine the learner engagement strategies and academic performance in online distance learning, Zone 3, Division of Zambales. A descriptive-correlational research design and quantitative analysis were employed in the study. The learner engagement strategies of intermediate learners in online distance learning were described and the academic performance tested its relationship. Findings revealed that learners are female, early adolescents, have smartphones, and are connected to the internet via WIFI broadband. The learners are highly engaged in the learner engagement strategies in online distance learning as learner-to-learner, learner- to- teachers and learner-to-content strategies in online distance learning. The learners obtained an outstanding academic performance. There is a significant difference in the learner engagement strategies in online distance learning as to learner-to-learner, learner- to- teachers and learner-to-content strategies in online distance learning when grouped according to the profile of the respondents in terms of age. There is a negligible relationship on the academic performance and learner engagement strategies of the learners. The proposed dissemination plan was developed based on the results of learner-to-learner, learner-to-teacher, and learner-to-content engagement strategies. The researcher recommends the following based on the findings that the teacher may still provide learning materials to be available to the learners. The teachers may encourage the learners to participate in the forum actively created so that they may ask questions about the lesson. The participation of the learners in virtual meetings during discussions is highly encouraged.